2015
DOI: 10.1161/atvbaha.115.305259
|View full text |Cite
|
Sign up to set email alerts
|

Choline Transporter-Like Protein-2

Abstract: Objective— In contrast to other antibodies involved in transfusion-related acute lung injury, anti–HNA-3a antibodies are incapable of inducing direct neutrophil activation and seem to interact with endothelial cells (ECs) primarily. In animal studies, anti–HNA-3a-mediated transfusion-related acute lung injury could be precipitated in the absence of neutrophils, but was stronger when neutrophils were present. In a different context the target protein of these antibodies, choline transporter-like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As it was previously described that HEK293 cells overexpressing SLC44A2 bind VWF in vitro, we sought to determine whether VWF could be altered in Slc44a2 −/− mice (8). In the FVB line, a non-significant 27% decrease in median plasma levels of VWF was observed in Slc44a2 −/− mice (p=0.1996) (Figure1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was previously described that HEK293 cells overexpressing SLC44A2 bind VWF in vitro, we sought to determine whether VWF could be altered in Slc44a2 −/− mice (8). In the FVB line, a non-significant 27% decrease in median plasma levels of VWF was observed in Slc44a2 −/− mice (p=0.1996) (Figure1C).…”
Section: Resultsmentioning
confidence: 99%
“…TRALI, like thrombosis, has a central role in its pathogenesis for endothelial cells and neutrophils, both of which express SLC44A2, in addition to several other tissues (4). Furthermore, a recent TRALI study described SLC44A2 to be a binding partner of VWF, a key molecule in hemostasis (8). Additionally, SLC44A2 has been associated with autoimmune hearing loss, due to its importance in hair cell viability (9).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary PMN infiltration has been described to occur in multiple animal models of TRALI [11,13,47,48,49,50,51,52,53,54,55,56,57]. Additionally, the abundance of PMNs has been observed in pulmonary tissue of TRALI patients upon autopsy [58,59].…”
Section: Neutrophil Involvement In Tralimentioning
confidence: 99%
“…Also other studies found PMN-mediated endothelial cell damage using an in vitro TRALI model in a setting of both non-antibody mediated TRALI [65] and antibody-mediated TRALI [61,66,67]. Furthermore, PMNs were found to interact with von Willebrand factor via choline transporter-like protein-2 (CTL-2), which allowed anti-HNA-3a antibody to induce signal transduction via CD11b/CD18, leading to PMN activation and agglutination [54]. This mechanism may aggravate endothelial cell damage in anti-HNA 3a antibody-mediated TRALI.…”
Section: Neutrophil Involvement In Tralimentioning
confidence: 99%
“…These antibodies bind to and aggregate granulocytes 32,33 . Bayat et al 34 showed that HNA3a antibody induces neutrophil activation through interaction with endothelial cells 34 requiring interaction of SLC44A2, von Willebrand Factor and CD11b/CD18 34 .…”
Section: 0 Discussionmentioning
confidence: 99%